Tinjauan Yuridis terhadap Surat Jual Beli Tanah Bersertifikat yang Dibuat oleh Kepala Desa - Saranani, Abdul Mutalib (Jurnal Ilmiah Dikdaya, 2022)
This research is entitled Juridical Review of Certificates of Sale and Purchase of Certified Land Made by Village Heads (Study of Case Decisions No: 2/Pdt.G/2018/PN.Unh). The objectives to be achieved in this study include to find out the factors causing the certificate of sale and purchase of certified land made by the village head in Konawe Regency and in addition to knowing the legal strength of the certified land sale and purchase certificate made by the village head in land disputes in the District Court Unaaha Konawe Regency. The results in this study are the factor in the occurrence of certificates of sale and purchase of certified land made by the village head, which is partly because some community members think that buying and selling land through PPAT requires quite a large fee, the mechanism is convoluted and the time period is too long, compared to the process of buying and selling land in front of the village head is considered easier to manage, costs less and the process is faster. Second, based on the Unaaha District Court Decision in civil case No.2/Pdt.G/2018/PN.UNH, before the panel of judges passed a decision regarding the land dispute between Hasbulah and Hombo and friends, first considered the plaintiff's claim, proving both the documents as well as the witnesses presented by the plaintiff, the fact was found that the land belonging to the plaintiff Hasbullah which was obtained from the sale and purchase of certified land for which the sale and purchase certificate was drawn up by the village head, is legally owned by the plaintiff Hasbullah. Thus the certificate of sale and purchase of certified land made by the village head has the legal force of proof in land disputes at the Unaaha District Court.